Biofuels : an Opportunity for Socio-economic Development and Cleaner Environment - Katwal, R. P. S.; Soni, P. L. (Indian Forester, 2003)
Both transport and industry depend heavily on diesel, which is produced from crude oil. However, reserves of crude oil are rapidly diminishing and the reliability and security of oil supplies has been of global concern. Depleting reserves of fossil fuel and increasing effect of environment pollution from these fuels demand eco.friendly alternatives. Biofuels (plant based fuel) can supplement or replace fossil fuels as they are renewable and environmentally safe. The most common type of biofuels that are being developed and used at present are bioethanol and biodiesel. After examining economic and operational aspects of blending of ethanol in petrol in terms oflogistic, marketing and distribution, Government of India decided to promote the use of 5% ethanol blend gasoline as a motor fuel in the country. To meet the energy needs of the country, annual consumption of petro diesel in 2000-2001 was about 38% of the total petroleum products. In view of economic, environmental and health benefits associated with use ofbiodiesel, planners have decided to develop biofuel programme in the country and targets are fixed to replace 5% and 10% of petro diesel by biodiesel by the year 2010 and 2015, respectively. Economics of production of biodiesel is a determining factor in making biofuel programme successful. The fatty oil derived from Jatropha curcas (Ratanjyot) and Pongamia pinnata (Karanj) are the excellent feed stock for biodiesel production. The paper presents on overview of biodiesel production using these species in Indian context and socio-economic development likely to occur.